Broadening anticancer spectrum by preprocessing and treatment of T- lymphocytes expressed FcγRI and monoclonal antibodies for refractory cancers - Tang, Lei; Sun, Qinyi; Li, Mengyuan; Yu, Xiaoxiao; Meng, Jinguo; Zhang, Yun; Ma, Yuxiao; Zeng, Aizhong; Li, Zhuolan; Liu, Yuanyuan; Xu, Xinyu; Guo, Wei (Frontiers in Immunology, 2024)
Background Chimeric antigen receptor T (CAR-T) cell therapies have achieved remarkable success in the treatment of hematological tumors. However, given the distinct features of solid tumors, particularly heterogeneity, metabolic aggressiveness, and fewer immune cells in tumor microenvironment (TME), the practical utility of CAR-T cells for solid tumors remains as a challenging issue. Meanwhile, although anti-PD-1 monoclonal antibody (mAb) has shown clinical efficacy, most mAbs also show limited clinical benefits for solid tumors due mainly to the issues associated with the lack of immune cells in TME. Thus, the infiltration of targeted immunological active cells into TME could generate synergistic efficacy for mAbs. Methods We present a combinational strategy for solid tumor treatment, which combines armored-T cells to express Fc-gamma receptor I (FcγRI) fragment on the surfaces for targeting various tumors with therapeutically useful mAbs. Choosing CD20 and HER-2 as the targets, we characterized the in vitro and in vivo efficacy and latent mechanism of the combination drug by using flow cytometry, ELISA and other methods. Results The combination and preprocessing of armored T-cells with corresponding antibody of Rituximab and Pertuzumab exerted profound anti-tumor effects, which is demonstrated to be mediated by synergistically produced antibody-dependent cellular cytotoxicity (ADCC) effects. Meanwhile, mAb was able to carry armored-T cell by preprocessing for the infiltration to TME in cell derived xenograft (CDX) model. Conclusions This combination strategy showed a significant increase of safety profiles from the reduction of antibody doses. More importantly, the present strategy could be a versatile tool for a broad spectrum of cancer treatment, with a simple pairing of engineered T cells and a conventional antibody.